2020
DOI: 10.6001/biologija.v66i1.4188
|View full text |Cite
|
Sign up to set email alerts
|

Extract of oats as a modulator of fatty acid composition of geese tissues in the conditions of physiological stress

Abstract: Feeding natural antioxidant supplements to animals and birds has multiple advantages over traditional synthetic vitamins of the antioxidant group. This study investigated the effect of the Avena satíva extract on the antioxidant status and fatty acid composition of liver tissues, the brain, and skeletal muscles of geese, live weight dynamics, and pterylographic parameters during physiological stress of formation of contour and juvenile feathers. It is confirmed that adding oat extract to the geese diet during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…More significant differences in the tissues of 49-day old geese of the control and experimental groups were determined for PUFA in the cardiac muscles (increases in the contents of linoleic and linolenic acids and decreases in the levels of arachidonic and docosahexaenoic acids). It has to be noted that according to the results published earlier, a similar effect of the extract was seen in the liver tissues as well (Danchenko et al, 2020).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…More significant differences in the tissues of 49-day old geese of the control and experimental groups were determined for PUFA in the cardiac muscles (increases in the contents of linoleic and linolenic acids and decreases in the levels of arachidonic and docosahexaenoic acids). It has to be noted that according to the results published earlier, a similar effect of the extract was seen in the liver tissues as well (Danchenko et al, 2020).…”
Section: Discussionsupporting
confidence: 71%
“…Research by Danchenko et al (2020) revealed specifics of changes in fatty acid composition in the tissues of the brain, liver and skeletal muscles of geese consuming extract of common oat. The research found abnormal fluctuations in fatty acid composition of lipids in these tissues during physiological loading with feather development.…”
Section: Introductionmentioning
confidence: 99%
“…Дослідження змін жирнокислотного складу (ЖКС) ліпідів тканин гусей під час формування контурного і ювенального пір'я дозволило визначити рівень впливу цього механізму на підвищення адаптивних потенцій гусей в зазначеному періоді їхнього розвитку. Результати досліджень ЖКС тканин гусей в цьому досліді було оприлюднено раніше [8]. Доведено, що саме під час формування контурного пір'я в 28-добових гусенят підвищення антиоксидантної активності тканин, і в тому числі й печінки, під впливом екстракту відбувалось на тлі різкого падіння як сумарного вмісту НЖК, так ненасиченості ЖК ліпідів.…”
Section: результати й обговоренняunclassified
“…У роботі [8] оприлюднено особливості змін жирнокислотного складу в тканинах мозку, печінки і скелетних м'язів гусей за дії екстракту вівса посівного. Встановлено аномальні коливання жирнокислотного складу ліпідів цих тканин під час фізіологічної напруги формування пір'я.…”
unclassified